(untitled) (Scientific Researches in Academia, 2024)
The performance of six litchi cultivars (namely “Shahi”, “McLean”, “Early Large Red”, “Muzaffarpur”, “China” and “Seedless”) on the physical and biochemical quality of fruits was evaluated. Fruit samples were collected at maturity during June from 15-year-old trees of Tropical Horticulture Centre, Nawalpur, Sarlahi, Nepal. There was a significant difference among the varieties. The fruit weight ranged from 18.15-35.04gm, percent recovery of flesh 63.73-83.41%, TSS 17.98-20.58%, and, total sugar 10-19.2%. Seedless variety showed the best performance i.e. highest fruit weight (35.04±4.25gm), percent recovery of flesh (83.41±4.4%), length (3.84±0.31cm), breadth (3.62±0.21gm) and TSS (20.335±0.77%). Therefore, litchi genotypes such as the Seedless variety may have a unique potential for further enrichment of genetic improvement in litchi germplasm.